2019
DOI: 10.1016/j.freeradbiomed.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Upstream signaling events leading to elevated production of pro-survival nitric oxide in photodynamically-challenged glioblastoma cells

Abstract: Nitric oxide (NO) generated endogenously by inducible nitric oxide synthase (iNOS) promotes growth and migration/invasion of glioblastoma cells and also fosters resistance to chemotherapy and ionizing radiotherapy. Our recent studies revealed that glioblastoma cell iNOS/NO also opposes the cytotoxic effects of non-ionizing photodynamic therapy (PDT), and moreover stimulates growth/migration aggressiveness of surviving cells. These negative responses, which depended on PI3K/Akt/NF-κB activation, were strongly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 70 publications
2
62
0
1
Order By: Relevance
“…These results are similar to the reported role of RA in colorectal cancer [33]. Numerous studies have shown that the PI3K/Akt/NF-κB pathway is closely related to HCC progression [34][35][36]. In line with these reports, our results showed that the PI3K/Akt/NF-κB signal pathway is involved in the anti-tumor effects of RA in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to the reported role of RA in colorectal cancer [33]. Numerous studies have shown that the PI3K/Akt/NF-κB pathway is closely related to HCC progression [34][35][36]. In line with these reports, our results showed that the PI3K/Akt/NF-κB signal pathway is involved in the anti-tumor effects of RA in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Based on non-glioma studies by Huang et al [49] , it was postulated that specific lysine acetylation on p65 is necessary for stimulating transcriptional activity. Fahey and Girotti [48] verified this by showing that acetylation of lysine-310 (p65-acK310) is substantially upregulated in photostressed U87 cells. Investigation of upstream signaling events revealed that p65-acK310 formation was dependent on phosphorylation-activation of PI3K, followed by Akt, and thence acetyltransferase p300.…”
Section: Underlying Mechanisms Of Inos/no Pro-survival Effectsmentioning
confidence: 84%
“…For mechanistic understanding, most efforts to date have focused on how iNOS/NO is upregulated rather than how NO signals for greater cell resistance or aggressiveness, although some progress has been made in the latter category. Working with U87 and U251 cells, Fahey and Girotti [48] found that transcription factor NF-κB played a seminal role in post-ALA/light iNOS induction leading to greater cell migration and invasion. Consistent with this, NF-κB subunit p65/Rel A of photostressed U87 cells translocated from cytosol to nucleus, where it participated in iNOS transcription [48] .…”
Section: Underlying Mechanisms Of Inos/no Pro-survival Effectsmentioning
confidence: 99%
See 2 more Smart Citations